Two pathways for the activation of small-conductance potassium channels in neurons of substantia nigra pars reticulata - Yanovsky, Yevgenij; Zhang, Weiyi; Misgeld, Ulrich (Neuroscience, 2005)
Neurons in substantia nigra pars reticulata express the messenger RNA for SK2 but not for SK3 subunits that form small-conductance, Ca2+-dependent K+ channels in dopamine neurons. To determine pathways for the activation of small-conductance, Ca2+-dependent K+ channels in substantia nigra pars reticulata neurons of rats and mice, we studied effects of the selective blocker of small-conductance, Ca2+-dependent K+ channels, apamin (0.01 or 0.3μM). Apamin diminished the afterhyperpolarization following each action potential and induced burst discharges in substantia nigra pars reticulata neurons. Apamin had a robust effect already at a low (10nM) concentration consistent with the expression of the SK2 subunit. Afterhyperpolarizations were also reduced by the Ca2+ channel blockers Ni2+ (100μM) and ω-conotoxin GVIA (1μM). Depletion of intracellular Ca2+ stores did not change the afterhyperpolarization. However, we observed outward current pulses that occurred independently from action potentials and were abrogated by apamin. Apart from a faster time course, they shared all properties with spontaneous hyperpolarizations or outward currents that ryanodine receptor-mediated Ca2+ release from intracellular stores induces in juvenile dopamine neurons. Sensitization of ryanodine receptors by caffeine silenced substantia nigra pars reticulata neurons. This effect was abolished by the depletion of intracellular Ca2+ stores. We conclude that SK2 channels in substantia nigra pars reticulata neurons are activated by Ca2+ influx through at least two types of Ca2+ channels in the membrane and by ryanodine receptor-mediated Ca2+ release from intracellular stores. Ryanodine receptors do not amplify small-conductance, Ca2+-dependent K+ channel activation by the Ca2+ influx during a single spike. Yet, ryanodine receptor-mediated Ca2+ release and, thereby, an activation of small-conductance, Ca2+-dependent K+ channels by intracellular Ca2+ are available for excitability modulation in these output neurons of the basal ganglia system.
Gesehen am 08.04.2021